Effect of age and plaque morphology on diagnostic accuracy of dual source multidetector computed tomography coronary angiography - Sunman, Hamza (Science Press, 2014)
BACKGROUND: Multidetector computed tomography (MDCT) coronary angiography represents one of the most exciting technological revolutions in cardiac imaging and it has been increasingly used in the diagnosis of coronary artery disease. The purpose of this study is to investigate the effect of age and coronary plaque calcification on diagnostic accuracy of MDCT. METHODS: The patients were examined by using dual-source MDCT and conventional coronary angiography. MDCT results were analyzed with regard to the severity (> 50% stenosis) and morphology (non-calcified, mixed, or calcified) of coronary atherosclerotic plaques evaluated in a 16-segment model. RESULTS: In total, 181 patients (94 men and 87 women) with 2,687 coronary artery segments were examined with MDCT. Ninety three patients were older than 65 years of age (group A, 42 men) and 88 were younger (group B, 52 men). Two-hundred nine coronary artery segments (7.2%) were excluded because of small distal coronary vessel segments and/or motion artifacts. The overall number of segments with non-diagnostic image quality was similar in both groups of patients. Of the 2,687 evaluated segments, 157 (5.8%) were significantly diseased, and 144 of them were correctly detected by MDCT. Diagnostic evaluation showed that the sensitivity, positive predictive value, specificity, and negative predictive value were 89.5%, 62.5%, 96.0%, and 99.2%, respectively in group A, and 95.2%, 64.8%, 97.5%, and 99.8% in group B, respectively. In addition, detailed segment-based analyses in coronary segments with non-calcified, mixed and calcified plaques in both groups were similar diagnostic accuracy. CONCLUSIONS: Very high diagnostic accuracy observed in this study suggests that MDCT coronary angiography could be a suitable diagnostic tool for not only younger patients but also for older patients.